Burkina Faso : Staff Report for the 2002 Article IV Consultation and Fifth Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines the 2002 Article IV Consultation and Fifth Review Under the Poverty Reduction and Growth Facility (PRGF) for Burkina Faso. Performance under the PRGF-supported program has been generally satisfactory, as all end-December 2001 quantitative performance criteria, benchmarks, and indicators were met, except for the indicator on current revenue. The IMF staff commends the authorities for vigorously pursuing the poverty reduction objectives imbedded in the Poverty Reduction Strategy Paper and for improving in social outcomes. However, further efforts are needed to improve the planning and execution of the poverty reduction strategy.